2014
DOI: 10.1021/es404240x
|View full text |Cite
|
Sign up to set email alerts
|

Humic Substances Enhance Chlorothalonil Phototransformation via Photoreduction and Energy Transfer

Abstract: The photodegradation of chlorothalonil, a polychlorinated aromatic fungicide widely used in agriculture, was investigated under ultraviolet-visible irradiation in the presence and absence of different humic substances that significantly enhance the chlorothalonil phototransformation. On the basis of a kinetic model, an analytical study, the effect of scavengers, the chlorothalonil phosphorescence measurement, and varying irradiation conditions, it was possible to demonstrate that this accelerating effect is du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
(98 reference statements)
1
31
0
2
Order By: Relevance
“…A range of techniques has been used to aid in the characterization of HS, particularly Fourier‐transform infrared spectroscopy, 13 C NMR spectroscopy, and, increasingly, synchrotron‐based Fourier‐transform infrared–attenuated total reflectance spectroscopy and carbon near edge X‐ray fine structure spectroscopy (Davis et al, 1999; Kulikova and Perminova, 2002; Solomon et al, 2005; Christl and Kretzschmar, 2007; Amir et al, 2010; Prietzel et al, 2018). The application of these techniques has contributed significantly to our knowledge of the mechanisms responsible for pesticide sorption to HS (Piccolo et al, 1996; Wang et al, 2011; Dutta et al, 2015).…”
Section: Modeling Of Metal Ion Binding In Soilsmentioning
confidence: 99%
“…A range of techniques has been used to aid in the characterization of HS, particularly Fourier‐transform infrared spectroscopy, 13 C NMR spectroscopy, and, increasingly, synchrotron‐based Fourier‐transform infrared–attenuated total reflectance spectroscopy and carbon near edge X‐ray fine structure spectroscopy (Davis et al, 1999; Kulikova and Perminova, 2002; Solomon et al, 2005; Christl and Kretzschmar, 2007; Amir et al, 2010; Prietzel et al, 2018). The application of these techniques has contributed significantly to our knowledge of the mechanisms responsible for pesticide sorption to HS (Piccolo et al, 1996; Wang et al, 2011; Dutta et al, 2015).…”
Section: Modeling Of Metal Ion Binding In Soilsmentioning
confidence: 99%
“…This result agrees with previous studies which observed little sensitized photoreaction when CDOM was excited with a wavelength longer than 450 nm (photon energy < 266 kJ/mol). 27,34 QY Spectrum of 1 O 2 . The QY of 1 O 2 constantly decreased with increasing light wavelength (Figure 4b), generally agreeing with the observations of the monochromatic approach using a high-power laser and other techniques, 31,35−38 and the 1 O 2 QY varied depending on the CDOM source.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This reaction might be an energy transfer or an electron/H atom transfer reaction. The energy level of 3 CT* was previously estimated to lay at 275 kJ mol -1 based on phosphorescence measurements at 77 K in pentane (Porras et al, 2014). This is lower than the energy level reported for phenol  314-334 kJ.mol -1 (Becker, 1969) making the energy transfer from 3 CT* to T unlikely.…”
Section: Interactions Between Ct and Thyme's Volatilesmentioning
confidence: 89%